2014
DOI: 10.1177/0040517514528561
|View full text |Cite
|
Sign up to set email alerts
|

Effect of raising cycles on mechanical, comfort, and hand properties of artificial suede

Abstract: This study evaluated the effect of the raising condition on the mechanical, comfort, and hand properties of artificial suede made of nylon/polyester microfibers, and identified those best suited for the consumer's needs. The suede became thicker and heavier; in addition, the wale density increased by repeated raisings as the base knits contracted and naps increased after a repeated raising process. Water vapor transmission decreased, but thermal resistance and water repellency increased. The increased number o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 11 publications
(13 reference statements)
0
10
0
Order By: Relevance
“…There is some research that already discussed on artificial leather such as on surface modification (Sakmat et al, 2015), processing (Roh et al, 2014), thermal and mechanical properties modification (Ma et al, 2019;Maia et al, 2017;Pimapunsri et al, 2017;Yang et al, 2017). And some paper has also studied the effect of k-value into the rheological behavior of plastisol (Zadhoush et al, 2004) and molecular weight distribution (Pepperl, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…There is some research that already discussed on artificial leather such as on surface modification (Sakmat et al, 2015), processing (Roh et al, 2014), thermal and mechanical properties modification (Ma et al, 2019;Maia et al, 2017;Pimapunsri et al, 2017;Yang et al, 2017). And some paper has also studied the effect of k-value into the rheological behavior of plastisol (Zadhoush et al, 2004) and molecular weight distribution (Pepperl, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…The KES-F test was used to assess the effects of fabric raisings on comfort, hand and mechanical properties of artificial suede. The increased number of raisings caused the suede to have a soft and smooth surface and improved perception of luxuriousness [27]. The hand properties of woven and knitted fabrics were investigated using the KES-F and frictional analyser tests and the KES-F results indicate that there is a good correlation between friction and tactile properties for knitted fabrics but not for woven fabrics [28].…”
Section: Introductionmentioning
confidence: 99%
“…2,5 The influence of the raising process on fabric hand, smoothness, and softness has been investigated in the finishing-related literature of textiles. 1,6,7 Matsudaira and Matsui 1 investigated the fabric properties, especially fabric handle, of polyester fabrics through the finishing stages and found that raising enhanced the fabric handle. Brooks 6 reported the results of the subjective assessment of raised woolen fabrics for smoothness, softness, and stiffness.…”
mentioning
confidence: 99%
“…For instance, the created air pores within the increased volume of the fabric structure improve the thermal insulation and warmth of the fabric. 2,3,7,8 Bueno et al. 2 described a tribological method for investigating the effects of raising and sanding on the surface characteristics of some woven and knitted fabrics.…”
mentioning
confidence: 99%